Flavonoid-based inhibitors of the Phi-class glutathione transferase from black-grass to combat multiple herbicide resistance. Issue 42 (13th October 2021) - Schwarz, Maria; Eno, Rebecca F. M.; Freitag-Pohl, Stefanie; Coxon, Christopher R.; Straker, Hannah E.; Wortley, David J.; Hughes, David J.; Mitchell, Glynn; Moore, Jenny; Cummins, Ian; Onkokesung, Nawaporn; Brazier-Hicks, Melissa; et al.
Abstract : Nature inspired flavonoid derivatives bind to AmGSTF1 and overcome herbicide resistance in multiple herbicide resistant (MHR) Black Grass. Abstract : The evolution and growth of multiple-herbicide resistance (MHR) in grass weeds continues to threaten global cereal production. While various processes can contribute to resistance, earlier work has identified the phi class glutathione- S -transferase ( Am GSTF1) as a functional biomarker of MHR in black-grass ( Alopecurus myosuroides ). This study provides further insights into the role of Am GSTF1 in MHR using a combination of chemical and structural biology. Crystal structures of wild-type Am GSTF1, together with two specifically designed variants that allowed the co-crystal structure determination with glutathione and a glutathione adduct of the Am GSTF1 inhibitor 4-chloro-7-nitro-benzofurazan (NBD-Cl) were obtained. These studies demonstrated that the inhibitory activity of NBD-Cl was associated with the occlusion of the active site and the impediment of substrate binding. A search for other selective inhibitors of Am GSTF1, using ligand-fishing experiments, identified a number of flavonoids as potential ligands. Subsequent experiments using black-grass extracts discovered a specific flavonoid as a natural ligand of the recombinant enzyme. A series of related synthetic flavonoids was prepared and their binding to Am GSTF1 was investigated showing a high affinity for derivatives bearing a O -5-decyl-α-carboxylate. Molecular modelling based on high-resolution crystal structures allowed a binding pose to be defined which explained flavonoid binding specificity. Crucially, high binding affinity was linked to a reversal of the herbicide resistance phenotype in MHR black-grass. Collectively, these results present a nature-inspired new lead for the development of herbicide synergists to counteract MHR in weeds.